The Role of the G6 in the Internal Security Policy of the European Union - Gruszczak, Artur (Roczniki Nauk Społecznych, 2024)
The present paper seeks to analyze the impact of the Group of Six (G6) on the area of internal security of the European Union. The G6 is an example of initiatives which were born outside the legal-institutional framework of the European Union yet were aiming to exert a significant influence on the political processes within the EU. The key research question raised in this paper is: What impact has the G6’s agenda got on policy-making in the EU’s internal security field? Methodology contains postfunctionalism as a theoretical framework. Research was based on qualitative methods, an analysis of primary sources and the subject literature. The findings point to the significant influence of the G6 as an informal forum for consultations and agenda-setting with regard to key matters of the EU’s internal security. The G6 supported the EU’s policy in the face of the most serious security challenges, taking advantage of the constructive compromise between the supranational effects of EU policy and the interests of the member states.